2011
DOI: 10.4161/cib.4.2.14491
|View full text |Cite
|
Sign up to set email alerts
|

Linking LIMK1 deficiency to hyperacusis and progressive hearing loss in individuals with Williams syndrome

Abstract: Williams syndrome (a.k.a. Williams-Beuren Syndrome) is a multisystem disorder caused by the hemizygous deletion of a 1.6 Mb region at 7q11.23 encompassing about 26 genes, including that encoding LIM kinase 1 (LIMK1). Individuals with Williams Syndrome manifest hyperacusis and progressive hearing loss, and hyperacusis early onset suggests that it could be associated with one of the deleted genes. Based on our results about the critical role of LIM kinases in the regulation of the motile responses of cochlear ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
2
11
0
4
Order By: Relevance
“…It encodes a serine/threonine kinase, which regulates outer hair cell motility by its effect on actin (Stanyon & Bernard, 1999). Matsumoto, Kitani, and Kalinec (2011) proposed that a deficiency of LIMK 1 might cause an increase in outer hair cell motility, leading to increased amplification of sound and thus to hyperacusis (Matsumoto, Kitani, & Kalinec, 2011). The interpretation of the startle reflex in hyperacusis is not clear.…”
Section: Williams Syndrome and A Possible Genetic Linkmentioning
confidence: 99%
See 1 more Smart Citation
“…It encodes a serine/threonine kinase, which regulates outer hair cell motility by its effect on actin (Stanyon & Bernard, 1999). Matsumoto, Kitani, and Kalinec (2011) proposed that a deficiency of LIMK 1 might cause an increase in outer hair cell motility, leading to increased amplification of sound and thus to hyperacusis (Matsumoto, Kitani, & Kalinec, 2011). The interpretation of the startle reflex in hyperacusis is not clear.…”
Section: Williams Syndrome and A Possible Genetic Linkmentioning
confidence: 99%
“…In addition to auditory anomalies such as hyperacusis (Attias, Raveh, Ben-Naftali, Zarchi, & Gothelf, 2008;Elsabbagh, Cohen, Cohen, Rosen, & Karmiloff-Smith, 2011;Levitin, Cole, Lincoln, & Bellugi, 2005;Matsumoto et al, 2011), other reported phenomena in Williams syndrome include auditory allodynia (Levitan & Bellugi, 1998;Levitan et al, 2005Levitan et al, , 2003Miani, Passon, Bracale, Barotti, & Panzolli, 2001). Cortical anatomical abnormalities have in part been attributed to reduced volume and altered sulcal morphology of the Sylvian fissure, atypical primary auditory cortex cytoarchitecture, and increased volume of the superior temporal gyrus.…”
Section: Dtimentioning
confidence: 99%
“…In addition, they are able to elongate and shorten at frequencies of up to 100 kHz-and presumably beyond that-after electrical stimulation (4,5). This motile response, usually referred to as OHC electromotility, is a crucial component of the cochlear amplifier, the active process that enhances sensitivity and frequency discrimination in the mammalian inner ear (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…OHCs were whole-cell voltage clamped with an Axon 200B amplifier using patch pipettes having initial resistances of 3-5 MΩ. Series resistances ranged from 5 to 20 MΩ [26,27]. All data acquisition and analysis were performed with a Windows-based patch clamp program, jClamp.…”
Section: Whole-cell Patch Clampmentioning
confidence: 99%